The impact of religious involvement on the relationship between religious orientation and religious coping. Issue 1 (2nd January 2021) - Hu, Xiaozhong; Cheng, Sanyin
ABSTRACT: This study explores the relationships among religious orientation, religious involvement, and religious coping among university students in mainland China. The AUIES-12, the religious involvement scale, and the brief RCOPE were administered to 977 undergraduate students from one comprehensive university. Results showed that: (1) religious orientation significantly predicted religious coping; (2) religious involvement significantly predicted religious coping; and, (3) religious involvement mediated the relationships between religious orientation and religious coping. The contributions, limitations and implications of this research are discussed.